An amperometric sensor readout chip and digital back-end with embedded integrator and redox potential generator for multi-analyte sensing applications. (March 2020) - Silverio, Angelito A.; Chung, Wen-Yaw; Tsai, Vincent F.S.; Cheng, Cheanyeh
Abstract: A fabricated amperometric sensor readout chip for interfacing with multiple electrochemical cells is presented. The chip incorporates a current integrator which can be used for charge determination and current accumulation for drift compensation. It also has a programmable redox potential generator. The front-end consists of a PMOS source input driven by a high gain OTA. It achieves very low input impedance and consequently, a wide current sensing range. The circuit utilizes pass elements acting as sensor enable for minimizing cross-talk. The current integrator utilizes a CCII+ with pre-settable gain. This is used to compensate for the sensor drift and degrading signal-noise-ratio whenever its enzyme is expended. The readout circuit was fabricated using TSMC 0.35 ​ ​μm technology. Digital interface was implemented onto an FPGA using the Altera 90 ​nm Cyclone II DE2 board. The system was tested using commercial two-electrode glucose and uric acid sensors, and a three-electrode uric acid biosensor. Experimentation confirms the functionality of the system using known analyte concentrations.